Literature Review: Exploration of Features Microsoft Word - Jalil, Abdul; Rosa, Firlana; Affandi, Rheinald; Aziz, Abdul; Saputra, Wahyu Nurkholis Hadi; Ridho, Atok Ainur (International Applied Science, 2024)
Microsoft Word is also said to be a word processing program in the form of functional application software to facilitate writing or documents in various formats. Microsoft Word also has various types of features and artificial intelligence built into it which aim to make word processing easier and faster. Apart from that, in Microsoft Word there is also security which functions to protect the information contained in the document. Microsoft Word is equipped with various features and intelligence that aim to simplify and speed up word processing and maintain the security of information in documents. This research uses the library observation method with data from national and international scientific articles from 2011 to 2023, with databases from Google Scholar and DOAJ. Research results found that Microsoft Word features include: automatic script tracking, artificial intelligence, Track Changes, and information security. Intelligence built into Word, such as the Editor feature, provides editing suggestions and document improvements using machine learning. Track Changes records changes to documents, automated temporary reference management features such as Mendeley help and Reference Manager in quotes. Security features include new methods of using cryptography and steganography to protect document content.